Integrating GenAI in Creating Digital Storytelling as STEAM-Based English Tenses Material on Social Media - Alfiandy Kamal; Muhammad Chairil Imran (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate the integration of GenAI in creating DSTs as a STEAM-based medium for learning English tenses and to determine students’ acceptance of the created DSTs by using a simplified R&D by Alessi. This method consists of three phases: planning, design, and development. During the phases, multiple GenAI tools were employed for activities such as scripting, image and audio generation, editing, and subtitling. The results show that each GenAI has its own role and produces different responses, which require a curation process to ensure pedagogical content and appropriateness. The DST was also validated by two experts in content and media using Aiken’s V, which confirmed strong validity (M = 0.98, M = 0.97). It was then disseminated through TikTok and Instagram. Furthermore, the thirty EFL learners participating in this study showed a significant improvement (p < 0.001) as determined by the Wilcoxon test. TAM results also showed a reliable score (0.87) and positive student acceptance (M = 4.12). These findings affirm that GenAI can effectively assist in creating DSTs, improve students’ tense understanding, and are positively received by students. The findings also provide a practical GenAI-assisted DST workflow for EFL-STEAM contexts.